Promoción de la salud (ps) en la globalidad (2012)
ABSTRACT: To unravel some theoretical and factual elements required to implement more effective health promotion strategies and practices in the field of health services whilst following the great challenges that globalization has imposed on the health systems, which are inevitably expressed in the local context (glocalization). Methodology: a narrative review taking into account the concepts of globalization and health promotion in relation to health determinants. The authors approach some courses of action and strategies for health promotion based on the social principles and universal values that guide health promotion, health service reorientation and primary healthcare, empowerment, social participation, and inter-sectoral and social mobilization. Discussion: the discussion focuses on the redirection of health promotion services in relation to the wave of health reforms that has spread throughout the world under the neoliberal rule. The author also discusses health promotion, its ineffectiveness, and the quest for renewal. Likewise, the author sets priorities for health promotion in relation to social determinants. Conclusion: the current global order, in terms of international relations, is not consistent with the ethical principles of health promotion. In this paper, the author advocates for the implementation of actions to change the social and physical life conditions of people based on changes in the use of power in society and the appropriate practice of politics in the context of globalization in order to achieve the effectiveness of the actions of health promotion.